Integrated teaching: its theoretical and Practical base - Do, Mạnh Cường (Journal of Technical Education Science, 2010)
The way teachers conduct their teaching chiefly depend on their teaching approach, learning theory, and the appropriate learning model. Unlike the traditional approach, as the competencebased training approach (CBT) has as its contents structure a system of capacities for solutions to productions tasks in practice, the theme of each lesson is not so much an individual notion or skill, but a competency or a concrete component of production capability. To proceed with the teaching, therefore, teachers need to base their teaching on appropriate theories and learning models (such as the experiential learning model) to build appropriate lessons/lectures. These are called integrated teaching.